Scents and Scent Ability: Can Snakes Identify Heterospecifics and Conspecifics Using Airborne Semiochemicals? - Rulon W. Clark; Harshita Vallabhaneni; Hana M. Koyama; Elisa J. Paider; Donald M. Walker; Jason W. Dallas (Journal of Chemical Ecology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The potential efficacy of continuous plantar foot cooling during relatively mild simulated occupational heat stress—a pilot study - Jason M. Keeler; Charlie Walker; Amanda Regester; Molly Heikkinen; Blair D. Johnson; Y. Sungtaek Ju; Lihua Jin; Zachary J. Schlader (European Journal of Applied Physiology, 2026)
Purpose To identify the effect size regarding glabrous skin foot cooling on core temperature, cognitive performance, and physical work capacity (PWC) during mild simulated occupational heat stress. Methods A pilot sample of twelve healthy adults (5 women) completed experimental visits in a 38.7 ± 0.7 ℃ and 46 ± 9% relative humidity environment that consisted of 60-minutes of steady-state upper body ergometry exercise followed by a 60-minute PWC test involving upper body ergometry while maintaining a rating of perceived exertion of 13 (“somewhat hard”). In one trial, participants stood with bare feet on cooled plates (17.7 ± 0.5 ℃) and in the other they were on noncooled plates (36.5 ± 0.1 ℃), with the order assigned in a block randomized manner. Results Core temperature increased during steady-state exercise (from 37.5 ± 0.3 to 37.6 ± 0.3 ℃, p < 0.003) and the PWC test (from 37.6 ± 0.3 to 37.9 ± 0.3 ℃, p < 0.001), but there was no difference between conditions (mean difference 0.03±0.18 ℃, p ≥ 0.592, d z =0.112). During the PWC test, there was no difference between conditions for mean power output ( p = 0.213, d z =0.184), with the final power outputs of 28 ± 9 W and 30 ± 9 W for control and cooling conditions, respectively. There were no condition effects for cognitive performance on any measure ( p ≥ 0.207, d z ≤0.405). However, foot cooling (+ 15 ± 9 bpm) reduced increases of heart rate during the PWC test compared to control (+ 21 ± 11 bpm, p = 0.013, d z =0.425). Conclusion Glabrous skin foot cooling has a relatively small effect on core temperature and PWC, but moderate effects on cognitive performance and heart rate during short duration (~ 3 h) mild heat stress.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A decision support tool for assessing entanglement risk to protected species from fixed-gear fisheries with applications to North Atlantic right whales (Eubalaena glacialis) in the Northwest Atlantic - Burton Shank; Alicia S. Miller; Laura Solinger; Michael J. Asaro; Douglas Sigourney; Alessandra Huamani; Marisa L. Trego; Crystal Franco; Jason J. Roberts; Jeffrey D. Walker; André L. Price; Mareike D. Duffing Romero; et al. (Frontiers in Marine Science, 2025)
Entanglement is one of the primary anthropogenic threats to the North Atlantic right whale ( Eubalaena glacialis ; right whale) whose habitat overlaps fixed-gear fishing grounds in the Northwest Atlantic with entanglements representing around half of the mortality and serious injury incidents. Right whale mortality has reached levels that require intervention under the Marine Mammal Protection Act, creating the need for a tool that can compare the relative benefits of risk reduction management measures under consideration. To address this need, National Marine Fisheries Service developed a Decision Support Tool (DST) which has undergone continued development since 2019 and is introduced here as the Woods Hole Analysis of Line Entanglement (WHALE) DST. This tool calculates relative risk as the product of (1) the density of endlines associated with fixed-gear fishing at a given location and month, (2) the entanglement severity that endlines pose based on the specific configuration of the gear, and (3) the estimated density of right whales at the given location and month. The model is novel in its capacity to quantify reductions in entanglement risk by simultaneously assessing a variety of overlapping management actions such as time/area closures, weakening of rope, and other adaptations of gear configurations that reduce endlines or make them less dangerous. We demonstrate the functionality of the WHALE DST by applying management actions implemented in 2021. While originally developed for right whale conservation, the WHALE DST is adaptable for evaluating spatiotemporal entanglement risk reduction for other protected species management and marine spatial planning activities.

Specialized metabolites of the herptile gut fungus, Basidiobolus - George F. Neuhaus; Ian A. Trautman; Richard M. Tehan; Lluvia Vargas-Gastélum; Alexander S. Romer; N. Reed Alexander; Marjan Ghotbi; Kylie C. Moe; Leila Shadmani; Javier F. Tabima; Jason E. Stajich; Donald M. Walker; et al. (Phytochemistry Letters, 2025)

What the Marine Strategy Framework Directive did and did not change for Chondrichthyes - Lydia Koehler; Paddy Walker; Irene Kingma; Simone Niedermüller; Jason Lowther (Marine Policy, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Functional Characterization of a Female-Biased Chemoreceptor of the Codling Moth (Cydia pomonella) Responding to Aldehydes and Other Volatile Compounds - Alberto Maria Cattaneo; Charles A. Kwadha; Heidi Pullmann-Lindsley; Anna L. Erdei; R. Jason Pitts; William B. Walker (Journal of Chemical Ecology, 2025)
With the advent of semiochemical-based control strategies used to mitigate damage of agricultural pest moths, many studies have focused on the function of male-specific putative pheromone receptors (PRs). In this investigation, we instead isolated, heterologously expressed, and functionally characterized a female-biased candidate PR, CpomOR22, from the codling moth, Cydia pomonella . Using transgenic Drosophila melanogaster for single sensillum recording (SSR) and gas-chromatographic SSR, we tested both synthetic ligands and various apple headspace extracts, identifying saturated and unsaturated aldehydes (nonanal, decanal, undecanal, dodecanal; ( Z )-4-undecenal and ( Z )-6-undecenal) among the most active ligands. Parallel experiments expressing CpomOR22 in Xenopus oocytes confirmed the binding of nonanal, decanal and undecanal and revealed lactones (γ-undecalactone and δ-dodecalactone) and several carboxylic acids as additional active compounds. The renowned ecological importance of aldehydes for the codling moth and the potential for newly identified ligands, such as lactones, may inform innovative control strategies based on novel semiochemicals to interfere with the female-specific chemosensory systems of this insect.

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

Distribution and disturbances of ditches across salt marshes of the Northeast U.S. with implications for management and restoration - Erin K. Peck; Julie E. Walker; Katherine V. Ackerman; Joel Carr; Maureen D. Correll; Zafer Defne; Linda A. Deegan; Mitchell J. Eaton; Neil K. Ganju; Mitch Hartley; Catherine Johnson; Jason Mercer; et al. (Journal of Environmental Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Long-term management of PFAS contaminated water using constructed floating wetlands: Opportunities, limitations, and implementation considerations - John Awad; Divina Navarro; Jason Kirby; Christopher Walker; Albert Juhasz (Critical Reviews in Environmental Science and Technology, 2024)

Genetic gain in yield of Australian faba bean since 1980 and associated shifts in the phenotype: Growth, partitioning, phenology, and resistance to lodging and disease - James B. Manson; Kedar N. Adhikari; Sara N. Blake; Samuel C. Catt; Matthew D. Denton; Lachlan Lake; Jason Brand; Cassandra Walker; Julian Taylor; Victor O. Sadras (Field Crops Research, 2024)

Advancing green space equity via policy change: A scoping review and research agenda - Alessandro Rigolon; Rexford Osei Owusu; Marisol Becerra; Yuan (Daniel) Cheng; Jon Christensen; James J.T. Connolly; C.N.E. Corbin; Jason A. Douglas; Mariela Fernandez; Viniece Jennings; Jennifer Ito; Lauren E. Mullenbach; et al. (Environmental Science & Policy, 2024)

Beyond closure: A literature review and research agenda for post-mining transitions - Thomas Measham; Jim Walker; Fiona Haslam McKenzie; Jason Kirby; Caroline Williams; Jillian D'Urso; Anna Littleboy; Agnes Samper; Rebecca Rey; Bryan Maybee; David Brereton; Guy Boggs (Resources Policy, 2024)

Fostering greater recognition of Caribbean traditional plant knowledge - Ina Vandebroek; Jason West; Kenneth Otero-Walker; Steve Maldonado Silvestrini (Trends in Ecology & Evolution, 2024)

Environmental and health impacts of functional graphenic materials and their ultrasonically altered products - Walker M. Vickery; Hunter B. Wood; Jason D. Orlando; Juhi Singh; Chenyun Deng; Li Li; Jing-Yi Zhou; Frederick Lanni; Aidan W. Porter; Stefanie A. Sydlik (NanoImpact, 2023)

Port-based seafarers’ welfare in Canada: resources and gaps - Jason Zuidema; Desai Shan; Kevin Walker; Alireza Jahanbakhsh (Marine Policy, 2023)

In vitro degradation and erosion behavior of commercial PLGAs used for controlled drug delivery - Jennifer Walker; Jason Albert; Desheng Liang; Jing Sun; Richard Schutzman; Raj Kumar; Cameron White; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2023)

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Governance in the Face of Extreme Events: Lessons from Evolutionary Processes for Structuring Interventions, and the Need to Go Beyond - Simon A. Levin; John M. Anderies; Neil Adger; Scott Barrett; Elena M. Bennett; Juan Camilo Cardenas; Stephen R. Carpenter; Anne-Sophie Crépin; Paul Ehrlich; Joern Fischer; Carl Folke; Nils Kautsky; et al. (Ecosystems, 2022)

Imaging cognitive fatigability in multiple sclerosis: objective quantification of cerebral blood flow during a task of sustained attention using ASL perfusion fMRI - Jason A. Berard; Zhuo Fang; Lisa A. S. Walker; Alyssa Lindsay-Brown; Leila Osman; Ian Cameron; Roxana Cruce; Greg O. Cron; Mark S. Freedman; Andra M. Smith (Brain Imaging and Behavior, 2020)

A COVID-19 Airway Management Innovation with Pragmatic Efficacy Evaluation: The Patient Particle Containment Chamber - Lauren M. Maloney; Ariel H. Yang; Rudolph A. Princi; Alexander J. Eichert; Daniella R. Hébert; Taelyn V. Kupec; Alexander E. Mertz; Roman Vasyltsiv; Thea M. Vijaya Kumar; Griffin J. Walker; Edder J. Peralta; Jason L. Hoffman; et al. (Annals of Biomedical Engineering, 2020)
The unique resource constraints, urgency, and virulence of the coronavirus disease 2019 pandemic has sparked immense innovation in the development of barrier devices to protect healthcare providers from infectious airborne particles generated by patients during airway management interventions. Of the existing devices, all have shortcomings which render them ineffective and impractical in out-of-hospital environments. Therefore, we propose a new design for such a device, along with a pragmatic evaluation of its efficacy. Must-have criteria for the device included: reduction of aerosol transmission by at least 90% as measured by pragmatic testing; construction from readily available, inexpensive materials; easy to clean; and compatibility with common EMS stretchers. The Patient Particle Containment Chamber (PPCC) consists of a standard shower liner draped over a modified octagonal PVC pipe frame and secured with binder clips. 3D printed sleeve portals were used to secure plastic sleeves to the shower liner wall. A weighted tube sealed the exterior base of the chamber with the contours of the patient’s body and stretcher. Upon testing, the PPCC contained 99% of spray-paint particles sprayed over a 90s period. Overall, the PPCC provides a compact, affordable option that can be used in both the in-hospital and out-of-hospital environments.

The pharmacokinetics of meropenem and piperacillin-tazobactam during sustained low efficiency haemodiafiltration (SLED-HDF) - Sine Donnellan; Daniel F. B. Wright; Jason A. Roberts; Stephen B. Duffull; John B. W. Schollum; Tracey L. Putt; Steven C. Wallis; Robert J. Walker (European Journal of Clinical Pharmacology, 2020)

Biophysical Submesoscale Processes in the Wake of Hurricane Ivan: Simulations and Satellite Observations - Travis A. Smith; Jason K. Jolliff; Nan D. Walker; Stephanie Anderson (Journal of Marine Science and Engineering, 2019)
Tropical cyclone induced phytoplankton productivity is examined using a tropical cyclone version of the Coupled Ocean/Atmosphere Mesoscale Prediction System (COAMPS®). A four-component Nutrient–Phytoplankton–Detritus biological model is integrated into COAMPS to create a fully integrated air-ocean-wave-biology model. This study investigates the upper ocean physical and biological states before and after Hurricane Ivan traversed the central Gulf of Mexico, in mid-September 2004. Elevated concentrations of surface chlorophyll-a appear in the simulation two days after the passage of the tropical cyclone, and these results are spatially and temporally coherent with Moderate Resolution Imaging Spectroradiometer (MODIS) satellite data for this time period. Model results reveal enhancement of chlorophyll-a in submesoscale filaments on the periphery of a warm-core eddy that are dominated by large values of lateral strain and relative vorticity at the surface. The vertical circulation of the filament, with its associated upward vertical motion, permits surface ventilation of cold, nitrogen-rich water and subsequent stimulation of primary biological production. Here, we show for the first time that coupled biological-physical submesoscale processes may be simulated via a fully integrated air-sea-wave-biology tropical cyclone model that provides a mechanistic explanation of the conspicuous features revealed in satellite ocean color imagery following Ivan.

Spatial and temporal changes in the frequency and magnitude of intense precipitation events in the southeastern United States - Walker J. Skeeter; Jason C. Senkbeil; David J. Keellings (International Journal of Climatology, 2019)
Intense precipitation events (IPE; 99th percentile) in the southeastern United States from 1950 to 2016 were analysed temporally, spatially, and synoptically. The study area was partitioned into latitudinal and physiographic regions to identify subregions that experienced significant changes in IPE frequency or intensity. Furthermore, the spatial synoptic classification (SSC) was used to ascertain what surface weather types are associated with IPEs. Additionally, in conjunction with the SSC, surface forcing mechanisms for the 30 most extreme subregional IPEs were studied to uncover the surface synoptic conditions responsible for IPEs. Results revealed that IPEs increased in frequency and intensity on an annual basis for the southeastern United States. Seasonal results indicated that IPE frequency only increased in the fall. Subregional results reveal that latitudinally, IPEs became more common in the northern latitudes of the study area, while physiographically, significant increases in IPE frequency were most pronounced in areas inland from the Atlantic Coastal Plain. An increase in the annual number of IPEs associated with moist tropical (MT) days was identified across the study area, but was more prevalent in the central and north central latitudinal regions, and areas inland from the Atlantic Coastal Plain outside of the Appalachian Mountains. This MT increase was possibly caused by more common northwards and inland intrusion of these types of IPEs. While moist moderate (MM) and transitional (TR) days were most commonly associated with IPEs, these weather types did not have significant trends. The surface forcing mechanisms most commonly associated with the strongest IPEs were tropical events, followed by stationary fronts and concentric low‐pressure systems.

Response of three arid zone floodplain plant species to inundation - Jason M. Nicol; George G. Ganf; Keith F. Walker; Ben Gawne (Plant Ecology, 2018)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

An Australian pyro-tornadogenesis event - Richard H. D. McRae; Jason J. Sharples; Stephen R. Wilkes; Alan Walker (Natural Hazards, 2013)

Conserved anchorless surface proteins as group A streptococcal vaccine candidates - Anna Henningham; Emiliano Chiarot; Christine M. Gillen; Jason N. Cole; Manfred Rohde; Marcus Fulde; Vidiya Ramachandran; Amanda J. Cork; Jon Hartas; Graham Magor; Steven P. Djordjevic; Stuart J. Cordwell; et al. (Journal of Molecular Medicine, 2012)

Nondestructive Evaluation of Hydrogel Mechanical Properties Using Ultrasound - Jason M. Walker; Ashley M. Myers; Mark D. Schluchter; Victor M. Goldberg; Arnold I. Caplan; Jim A. Berilla; Joseph M. Mansour; Jean F. Welter (Annals of Biomedical Engineering, 2011)

Population structure and genetic diversity of greater sage-grouse (Centrocercus urophasianus) in fragmented landscapes at the northern edge of their range - Krista L. Bush; Christopher K. Dyte; Brendan J. Moynahan; Cameron L. Aldridge; Heather S. Sauls; Angela M. Battazzo; Brett L. Walker; Kevin E. Doherty; Jason Tack; John Carlson; Dale Eslinger; Joel Nicholson; et al. (Conservation Genetics, 2011)

Hydrological and biogeochemical controls on the timing and magnitude of nitrous oxide flux across an agricultural landscape - MICHAEL J. CASTELLANO; JOHN P. SCHMIDT; JASON P. KAYE; CHARLES WALKER; CHRIS B. GRAHAM; HENRY LIN; CURTIS J. DELL (Global Change Biology, 2010)
Anticipated increases in precipitation intensity due to climate change may affect hydrological controls on soil N 2 O fluxes, resulting in a feedback between climate change and soil greenhouse gas emissions. We evaluated soil hydrologic controls on N 2 O emissions during experimental water table fluctuations in large, intact soil columns amended with 100 kg ha −1 KNO 3 ‐N. Soil columns were collected from three landscape positions that vary in hydrological and biogeochemical properties ( N = 12 columns). We flooded columns from bottom to surface to simulate water table fluctuations that are typical for this site, and expected to increase given future climate change scenarios. After the soil was saturated to the surface, we allowed the columns to drain freely while monitoring volumetric soil water content, matric potential and N 2 O emissions over 96 h. Across all landscape positions and replicate soil columns, there was a positive linear relationship between total soil N and the log of cumulative N 2 O emissions ( r 2 = 0.47; P = 0.013). Within individual soil columns, N 2 O flux was a Gaussian function of water‐filled pore space (WFPS) during drainage (mean r 2 = 0.90). However, instantaneous maximum N 2 O flux rates did not occur at a consistent WFPS, ranging from 63% to 98% WFPS across landscape positions and replicate soil columns. In contrast, instantaneous maximum N 2 O flux rates occurred within a narrow range (−1.88 to −4.48 kPa) of soil matric potential that approximated field capacity. The relatively consistent relationship between maximum N 2 O flux rates and matric potential indicates that water filled pore size is an important factor affecting soil N 2 O fluxes. These data demonstrate that matric potential is the strongest predictor of the timing of N 2 O fluxes across soils that differ in texture, structure and bulk density.

Planning Strategies for Community Wildfire Defense Design in Florida - Robert Brzuszek; Jason Walker; Timothy Schauwecker; Chris Campany; Marc Foster; Steve Grado (Journal of Forestry, 2010)
New community developments in the wildland-urban interface can be planned to minimize loss of property and life to wildfire through multiple defensive strategies. This research examines three communities impacted by the 1998 Florida wildfires and compares the physical context and development patterns of these communities to three recently designed Florida subdivisions that incorporate Firewise principles. Analysis of the relationship of wildfires to the physical context and development patterns of affected residential communities provides the framework by which the two groups of communities are compared. Findings show that incorporating multiple defensive strategies in community planning, including taking advantage of road location, utility corridors, greenbelts, and existing wetlands, may be effective in wildfire defense. The comparative analysis concludes with design and layout considerations for community development in the southeastern United States.

Scalar effects of vegetation on bird communities in an urbanizing desert ecosystem - Jason S. Walker; Eyal Shochat (Urban Ecosystems, 2010)

Identification, Synthesis and Field Testing of (3Z,6Z,9Z)-3,6,9-Henicosatriene, a Second Bioactive Component of the Sex Pheromone of the Autumn Gum Moth, Mnesampela privata - Paul W. Walker; Geoff R. Allen; Noel W. Davies; Jason A. Smith; Peter P. Molesworth; Anna Nilsson; Fredrik Andersson; Erik Hedenström (Journal of Chemical Ecology, 2009)

Proteomic and phenotypic profiling of the amphibian pathogen Batrachochytrium dendrobatidis shows that genotype is linked to virulence - MATTHEW C. FISHER; JAIME BOSCH; ZHIKANG YIN; DAVID A. STEAD; JANET WALKER; LAURA SELWAY; ALISTAIR J. P. BROWN; LOUISE A. WALKER; NEIL A. R. GOW; JASON E. STAJICH; TRENTON W. J. GARNER (Molecular Ecology, 2009)
Population genetics of the amphibian pathogen Batrachochytrium dendrobatidis ( Bd ) show that isolates are highly related and globally homogenous, data that are consistent with the recent epidemic spread of a previously endemic organism. Highly related isolates are predicted to be functionally similar due to low levels of heritable genetic diversity. To test this hypothesis, we took a global panel of Bd isolates and measured (i) the genetic relatedness among isolates, (ii) proteomic profiles of isolates, (iii) the susceptibility of isolates to the antifungal drug caspofungin, (iv) the variation among isolates in growth and phenotypic characteristics, and (v) the virulence of isolates against the European common toad Bufo bufo . Our results show (i) genotypic differentiation among isolates, (ii) proteomic differentiation among isolates, (iii) no significant differences in susceptibility to caspofungin, (iv) differentiation in growth and phenotypic/morphological characters, and (v) differential virulence in B. bufo . Specifically, our data show that Bd isolates can be profiled by their genotypic and proteomic characteristics, as well as by the size of their sporangia. Bd genotypic and phenotypic distance matrices are significantly correlated, showing that less‐related isolates are more biologically unique. Mass spectrometry has identified a set of candidate genes associated with inter‐isolate variation. Our data show that, despite its rapid global emergence, Bd isolates are not identical and differ in several important characters that are linked to virulence. We argue that future studies need to clarify the mechanism(s) and rate at which Bd is evolving, and the impact that such variation has on the host–pathogen dynamic.

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Three-dimensional reconstruction of the flow in a human left heart by using magnetic resonance phase velocity encoding - Peter G. Walker; Gregory B. Cranney; Randall Y. Grimes; Jason Delatore; Joseph Rectenwald; Gerald M. Pohost; Ajit P. Yoganathan (Annals of Biomedical Engineering, 1995)